The hereditary N363K POLE exonuclease mutant extends PPAP tumor spectrum to glioblastomas by causing DNA damage and aneuploidy in addition to increased mismatch mutagenicity. Issue 2 (11th March 2023) - Labrousse, Guillaume; Vande Perre, Pierre; Parra, Genis; Jaffrelot, Marion; Leroy, Laura; Chibon, Frederic; Escudie, Frederic; Selves, Janick; Hoffmann, Jean-Sebastien; Guimbaud, Rosine; Lutzmann, Malik
Abstract: The exonuclease domain of DNA polymerases epsilon's catalytic subunit (POLE) removes misincorporated nucleotides, called proofreading. POLE-exonuclease mutations cause colorectal- and endometrial cancers with an extreme burden of single nucleotide substitutions. We recently reported that particularly the hereditary POLE exonuclease mutation N363K predisposes in addition to aggressive giant cell glioblastomas. We knocked-in this mutation homozygously into human cell lines and compared its properties to knock-ins of the likewise hereditary POLE L424V mutation and to a complete proofreading-inactivating mutation (exo-null). We found that N363K cells have higher mutation rates as both L424V- or exo-null mutant cells. In contrast to L424V cells, N363K cells expose a growth defect, replication stress and DNA damage. In non-transformed cells, these burdens lead to aneuploidy but macroscopically normal nuclei. In contrast, transformed N363K cells phenocopy the enlarged and disorganized nuclei of giant cell glioblastomas. Taken together, our data characterize a POLE exonuclease domain mutant that not only causes single nucleotide hypermutation, but in addition DNA damage and chromosome instability, leading to an extended tumor spectrum. Our results expand the understanding of the polymerase exonuclease domain and suggest that an assessment of both the mutational potential and the genetic instability might refine classification and treatment of POLE-mutated tumors.